Perlindungan Hukum terhadap Masyarakat yang Diserang Buaya pada Habitat Buaya di Nusa Tenggara Timur - Radhi Renault Salmun; Jimmy Pello; Bhisa Vitus Wilhelmus (International Forum of Researchers and Lecturers, 2024)
Conflicts between humans and wild crocodiles still occur frequently in East Nusa Tenggara. Conflicts often occur with residents who live on coastlines and river estuaries, where most of the population earn their living as fishermen and farmers. The objectives of this research are: (1) Want to know the form of legal protection for people who are attacked by crocodiles in crocodile habitats. (2) Want to know the pattern of conflict management between humans and crocodiles in their habitat. This research is a type of empirical juridical research, or what is called field research, namely examining applicable legal provisions and what happens in reality in society. Empirical juridical research is legal research regarding the application or implementation of normative legal provisions in action in every legal event that occurs in society. The results of this research show: (1) Legal protection that protects every human right that is attacked by a crocodile has been clearly regulated in law number 5 of 1990, government regulation number 7 of 199 9, government regulation number 13 of 1994, and ministerial regulations forestry number P.08 of 2008. (2) Efforts to overcome conflict between crocodiles and humans have been carried out by establishing a SATGAS or task force for dealing with conflict between humans and wild animals and consists of two units, where one unit is tasked with dealing with the community and the other unit tasked with dealing with wild animals. There are also several government agencies in it to respond to reports quickly and handle them according to SOPs or standard operational procedures for handling conflicts between humans and wild crocodiles which serve as standard guidelines for handling conflicts reported by the public. As well as efforts from the government, there have also been short-term efforts such as outreach and long-term efforts such as conducting more in-depth research on crocodiles. Based on the results of this research, it is hoped that there will be awareness from all components, both society and government, so as not to excessively convert land so that it destroys the natural habitat of crocodiles and causes crocodiles to escape into public areas.